Membangun Tubuh Kristus dalam Kajian Teologis Calvin tentang Gereja yang Kelihatan dan Tidak Kelihatan - Roos Jermia Helena Lumi (Jurnal Salvation, 2026)
Abstract: Since the beginning of the church, various thoughts have emerged in order to understand what the church really is. The mention of the church as a body of Christ dominates every thought that speaks about the church itself.    As time went by, it was found that ideas about the church continued to develop, including about the visible and invisible church. These two concepts are worthy and remain interesting to discuss. Therefore, the author of this article attempts to present here a study of this matter in relation with church as a Body of Christ which must continue to be built as long as the life of God’s people continue in this world. Starting from Calvin’s study about visible and invisible church, here we will explain the importance of the church as the body of Christ which is built spiritually and institutionally or organizationally to further emphasize the presence of the church in this world. The author uses several methods to support the writing of this article. Abstrak: Pemahaman mengenai gereja sebagai Tubuh Kristus serta konsep gereja yang kelihatan dan tidak kelihatan merupakan tema penting dalam eklesiologi. Meskipun demikian, integrasi pemikiran Calvin mengenai kedua konsep tersebut dalam kerangka pembangunan gereja sebagai Tubuh Kristus belum memperoleh perhatian yang memadai. Penelitian ini bertujuan menganalisis pemikiran teologis Calvin tentang gereja yang kelihatan dan tidak kelihatan serta implikasinya bagi pembangunan gereja. Penelitian menggunakan metode kualitatif dengan pendekatan studi literatur yang dianalisis secara deskriptif-analitis. Hasil penelitian menunjukkan bahwa gereja merupakan satu kesatuan universal di bawah Kristus sebagai Kepala, sedangkan dimensi gereja yang kelihatan dan tidak kelihatan saling melengkapi dalam mewujudkan identitas spiritual dan kehadiran gereja di dunia. Penelitian ini memberikan kontribusi teologis bagi pembangunan gereja yang seimbang antara aspek spiritual dan institusional.